Severe deep white matter lesions and outcome in elderly patients with major depressive disorder: follow up study. Issue 7164 (10th October 1998) - O'Brien, John; Ames, David; Chiu, Edmond; Schweitzer, Isaac; Desmond, Patricia; Tress, Brian
Abstract: Objective To determine the difference in outcome among elderly people with major depression who do and do not have severe white matter lesions on magnetic resonance imaging. Design Follow up study. Setting Two psychiatric and two general hospitals in Melbourne, Australia. Subjects 60 depressed subjects aged over 55 referred to hospital psychiatric services with major depressive disorder meeting American Psychiatric Association (DSM-IIIR) criteria. Main outcome measure Proportion with good outcome as determined by full recovery from initial illness and no evidence of depressive relapse or cognitive decline during follow up among those with and without lesions. Results Mean (SD) follow up was 31.9 (9.9) months. Survival analysis showed a significant effect of severe lesions on time to poor outcome (P=0.04), with median survival 136 days in those with severe lesions compared with 315 days in those without. Conclusion Severe white matter change on magnetic resonance imaging is associated with poor outcome in elderly depressed subjects.